2017
DOI: 10.1080/15412555.2017.1342233
|View full text |Cite
|
Sign up to set email alerts
|

Should Patients Switched from D to B in the GOLD 2017 Classification be Discontinued from Inhaled Corticosteroids?

Abstract: Inhaled corticosteroids (ICSs) are the cornerstone of the treatment of asthma, but their role in COPD is limited. Several guidelines recommend their use in patients with severe airflow limitation, frequent exacerbations and asthma-COPD overlap (ACO), while the previous GOLD document recommended ICS for patients with high risk of exacerbations and a high level of symptoms (group D). Following the changes in the GOLD document 2017 update, in which impaired lung function is no longer considered as a determinant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…It was concluded that ICS withdrawal can have a deleterious effect in COPD patients with severe airflow limitation, at least one moderate-to-severe exacerbation in the preceding year, and high peripheral blood eosinophilic count (4% or greater or ≥ 300 cell/µL). Harlander et al 21 observed that with the change in COPD classification of severity from GOLD 2013 to GOLD 2017, many patients would move from group D to group B. In fact, the GOLD 2017 classification did not take into account any more the severity of airflow limitation as a factor increasing, per se, the risk of exacerbations.…”
Section: Eosinophils In Peripheral Bloodmentioning
confidence: 99%
See 2 more Smart Citations
“…It was concluded that ICS withdrawal can have a deleterious effect in COPD patients with severe airflow limitation, at least one moderate-to-severe exacerbation in the preceding year, and high peripheral blood eosinophilic count (4% or greater or ≥ 300 cell/µL). Harlander et al 21 observed that with the change in COPD classification of severity from GOLD 2013 to GOLD 2017, many patients would move from group D to group B. In fact, the GOLD 2017 classification did not take into account any more the severity of airflow limitation as a factor increasing, per se, the risk of exacerbations.…”
Section: Eosinophils In Peripheral Bloodmentioning
confidence: 99%
“…In fact, the GOLD 2017 classification did not take into account any more the severity of airflow limitation as a factor increasing, per se, the risk of exacerbations. The authors 21 conclude that withdrawal of ICS would be feasible in the group of patients moving from group D to B with the exclusion of patients with a suspected asthma-COPD overlap (ACO) and those with high peripheral blood eosinophils, suggesting ≥ 300 cells/µL as a cut-off count.…”
Section: Eosinophils In Peripheral Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Finally, eosinophil count cutoffs have been a controversial issue. 10,62 Authors of a recent review reported several barriers to the use of blood eosinophils to predict response to ICS therapy (eg, comorbidities, effort needed to calculate eosinophil counts, diurnal variation in individual blood eosinophil levels, and current medications and treatment) and recommended caution in its use as a biomarker. 63 Despite these inconsistencies, GOLD 2020 generally recommends blood eosinophil counts ≥300 cells/mL as a threshold for deciding ICS-based therapy; a threshold of ≥100 cells/mL can be considered in patients who have experienced ≥2 moderate exacerbations/year or ≥1 severe exacerbation requiring hospitalization in the preceding year.…”
Section: Eosinophils As Markers Of Response To Icsmentioning
confidence: 99%
“…In addition, following the changes in the GOLD document 2017 update, in which impaired lung function is no longer considered as a determinant of exacerbation risk, a A c c e p t e d M a n u s c r i p t high number of COPD patients can now be labeled as group B (low risk of exacerbations and high level of symptoms) instead of D, and hence, no longer fulfill the indication for ICS. Since long-term therapy with ICS can result in side effects, the withdrawal of this treatment should be considered in this group of patients [21]. There is often a over-prescription of ICSs in stable COPD patients, particularly in COPD grades A or B, with considerable potential for harm [22,23] but there is also often, particularly in general practice, a misdiagnosis of bronchial asthma as COPD grades A or B [24][25][26][27][28].…”
Section: Several Large Controlled Clinical Trials Of Inhaled Combinatmentioning
confidence: 99%